Chaos in Discrete Dynamical Systems: A Visual Introduction in 2 Dimensions - Abraham (Ralph H); Gardini (Laura); Mira (Christian) (1997)
Discrete Dynamical Systems
22.5
Keywords: Discrete Dynamical Systems